Analysis Of The Online Performance Management System (Smk) Implementation In The Directorate Of Special Criminal Reserve Of The Bengkulu Regional Police - Khoiril Akbar; Ridwan Nurazi; Slamet Widodo (UNIB Press, 2023)
The police online performance management system termed SMK is an electronic application to appraise work performances of the police officers in Indonesia. The system is to accommodate the reform policy made by the Indonesian National Police headquarter and have to implemented to all work units. The purpose of this study, therefore, is to describe the implementation of the police performance management system electronically consisted of the performance planning, performance monitoring, performance implementation, performance evaluation and submission of objections to the performance appraisal. The police officers who worked at the Directorate of Special Criminal Investigation in Bengkulu Regional Police headquarter were chosen as the subject for the study. A set of questionnaires was distributed to the subject as the respondents to collect information about their perceptions on the SMK implementation. Data gathered were analyzed using the descriptive statistics of mean, percentage, and frequency. The results indicate that systematically, the Directorate of Special Criminal Investigation followed the procedures of the performance appraisal very well on the five aspects assessed. However, practically, some procedures were missing. The aspect of performance planning was according to the procedure but from the indicators planned was written and formulated by the staff of each unit referred to the assessment indicators for the past period. The performance monitoring aspect was carried out from time to time, which was at the end of each semester. The implementing of the procedural assessment had been based on the assessment indicators in the form of generic factors and specific factors that have been agreed upon. The Evaluation of the performance appraisals, both the outstanding polices and the polices committing violations had been carried out in accordance with the rules. No one submitted the objections regarding the performance evaluation results. It needs a strong commitment to obey the rules. The implications and the suggestions are discussed. Keywords: Performance Management System, Performance Assessment, Directorate of Special Criminal Investigation, Regional Police